DNA Profiles of local herbs in Sarawak - Rosmawati, Saat; Zuliza, Ahmad; Siti Izyan Liyana, Kamarol; Hasneza, Iboi (Department of Wildlife and National Parks Peninsular Malaysia, 2024)
Many of the local herbs have commonly being used as folk medicines to treat among others; hepatitis, bronchitis, cough associated with pneumonia, jaundice, chest pain, snake bite, insect bite, rheumatism, anti-malaria and various stomach diseases. Some of these medicinal plants were shown to possess bioactive compounds against such as microbial activity, tumour activity, diabetic activity and diarrheal activity, which they have the potential to be explored in the production of novel drugs for pharmaceutical applications. Identification of the plants has been primarily based on morphology and similar looking plants may not be distinguished. A DNA profile can act as a signature for a particular plant species, whereby different species will have a different profile pattern. Hence, the profile can be used for identification and authentication of the plant species. Subsequently, it may be used as reference for pharmaceutical purposes. Variations within the plant species may also be detected by simply looking at the profile patterns. Three common local herbs, namely, Elephantopus scaber, Ageratum conyzoides and Blumea balsamifera are discussed. Their DNA profiles were generated using ISSR-PCR and RAPD-PCR.